Effects of moderate irrigation on vegetative growth and productive parameters of Monastrell vines grown in semiarid conditions - De la Hera-Orts, M.L.=700 1 Martinez-Cutillas, A.; Lopez-Roca, J.M.
(Es, En)
ilus., 34 ref.
Keywords: VIÑA; RIEGO; POTENCIAL HIDRICO DEL SUELO; FOTOSINTESIS; PRODUCCION; ESPAÑA; CONDUCTANCIA ESTOMATICA